Surveillance of antibody to measles, mumps, and rubella by age. Issue 6651 (24th September 1988) - Morgan-Capner, P.; Wright, J.; Miller, C. L.; Miller, E.
Abstract : Before the introduction of measles, mumps, and rubella vaccine a survey was carried out to measure antibody prevalence to the three viruses by age. A total of 8716 samples of serum collected by five public health laboratories in different parts of England during 1986-7 were tested. Despite the current measles vaccination programme 60% of children aged 1-2 years did not have measles antibody and over 80% did not have antibodies to mumps and rubella. In the 3-4 year age group 17% of the children were susceptible to measles, 55% to mumps, and 73% to rubella. The results suggest that vaccinating children early in the second year of life will be necessary to eliminate the three diseases. The survey provides baseline data for continuing surveillance of the immediate and long term effects of the new vaccination strategy.